(untitled) (Journal of Economic Research & Business Administration, 2015)
The meaning, content and main components of sustainable development are represented in the paper. The necessity of sustainable development principles, implementation of “Green” economy standards is shown in the paper. Author represents analysis of transition to new model of sustainable development in the Republic of Kazakhstan. Main difficulties and problems on this way are described in the paper. The necessity of sustainable development principles,implementation of “Green” economy standards is shown in the paper. Author represents analysis of transition to new model of sustainable development in the Republic of Kazakhstan. Main difficulties and problems on this way are described in the paper. The article reveals the issue of environmental regulation in the Republic of Kazakhstan. A concept of environmental regulation is represented in the paper. Author has studied the characteristics of environmental regulation in the Republic of Kazakhstan, the role of institutions in the transition to sustainable development in the Republic.